Rotationplasty Salvage Procedure as an Effective Alternative to Femoral Amputation in an Adult With a History of Osteosarcoma: A Case Report and Review - Gaillard, Jean; Fouasson-Chailloux, Alban; Eveno, Dominique; Bokobza, Guillaume; Da Costa, Marta; Heidar, Romain; Pouedras, Marie; Nich, Christophe; Gouin, François; Crenn, Vincent (Frontiers in Surgery, 2022)
Rotationplasty or Borggreve-Van Ness surgery is lower limb salvage surgery, indicated mainly in the management of femoral bone sarcoma and congenital femur malformations in children. It can also be an interesting surgery option for managing chronic osteoarticular infections, or in cases of non union when curative therapy is no longer an option, as an alternative to femoral amputation. The principle of this surgery is to remove the affected knee and to apply a rotation of 180° to the distal part of the lower limb in order to give the ankle the function of a neo-knee. With the help of an adapted prosthesis, the aim is to allow patients to resume their social and professional activities by keeping most of their lower limb, thus avoiding the known complications of amputation (ghost limb pain, proprioceptive deficit, psychological disorders). Nevertheless, this surgery is complex and exceptional, with vascular, infectious, and psychological risks - the chimeric aspect of the lower limb may cause significant ill-being for the patient. This article reports the case of a 38-year-old patient consulting for management of a complex septic distal femoral non-union following osteosarcoma considered as being in remission. The patient underwent rotationplasty surgery on his left lower limb, with very good functional results and no surgical revision to date. In light of this particular case, we propose a didactic overview of the literature data concerning this surgery, especially in adulthood.